2016
DOI: 10.1002/adma.201604623
|View full text |Cite
|
Sign up to set email alerts
|

Significant Radiation Tolerance and Moderate Reduction in Thermal Transport of a Tungsten Nanofilm by Inserting Monolayer Graphene

Abstract: Tungsten-graphene multilayer composites are fabricated using a stacking method. The thermal resistance induced by the graphene interlayer is moderate. An ion-implantation method is used to verify the radiation tolerance. The results show that graphene inserted among tungsten films plays a dominant role in reducing radiation damage. Furthermore, the performance of different tungsten period-thicknesses in radiation tolerance is systematically analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…Comparing with inner grains, GBs are favored nucleation sites for He bubbles. Such irradiation induced bubbles prefer alignment and distribution along the GBs . As the local concentration of He increases, the He bubble formation mechanism appears to have three distinct stages, including (a) He bubble formation along GB, (b) He bubble chain formation inside grain and (c) ribbon‐like He bubble formation inside grain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing with inner grains, GBs are favored nucleation sites for He bubbles. Such irradiation induced bubbles prefer alignment and distribution along the GBs . As the local concentration of He increases, the He bubble formation mechanism appears to have three distinct stages, including (a) He bubble formation along GB, (b) He bubble chain formation inside grain and (c) ribbon‐like He bubble formation inside grain.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, enhanced radiation resistance to amorphization was observed for nanostructured MgGa 2 O 4 , yttria stabilized zirconia (YSZ), and Gd 2 (Ti 0.65 Zr 0.35 ) 2 O 7 powder . Additionally, improved radiation tolerance to swelling and hardening caused by He bubble was also observed for nanostructured steel, tungsten film, and Fe–Cr–Ni alloy . Nevertheless, thus far, the exact role of GB and/or grain size in (a) structural orderness or amorphization, (b) cell volume expansion, and (c) bubble formation induced by He irradiation for the A 2 B 2 O 7 ceramic, remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, studies have shown that interfaces play a positive role in helium accumulation inhibition. 21,22 For example, interfaces can reduce the He bubble density during irradiation of solid-state materials. 21,22 Grain boundaries are found to play a similar role as that of interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…This was because the graphene interface absorbed radiation defects spontaneously caused by cascade collisions before achieving self-repair. A He ion implantation experiment in graphene/W multi-layer materials revealed that the insertion of graphene both reduced radiation damage and made He bubbles less likely to form [25].…”
Section: Introductionmentioning
confidence: 99%